2022
DOI: 10.3390/cancers14020344
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Value of the CA19-9 and Bilirubin Ratio in Patients with Pancreatic Cancer, Distal Bile Duct Cancer and Benign Periampullary Diseases, a Novel Approach

Abstract: Distinction of pancreatic ductal adenocarcinoma (PDAC) in the head of the pancreas, distal cholangiocarcinoma (dCCA), and benign periampullary conditions, is complex as they often share similar clinical symptoms. However, these diseases require specific management strategies, urging improvement of non-invasive tools for accurate diagnosis. Recent evidence has shown that the ratio between CA19-9 and bilirubin levels supports diagnostic distinction of benign or malignant hepatopancreaticobiliary diseases. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…CA19-9 is the only serological tumor biomarker approved by the FDA for pancreatic cancer, which is far from ideal. CA19-9 may give false positive results in benign pancreaticobiliary diseases, and is not expressed in about 10% of the Caucasian population [ 11 , 12 , 13 , 14 , 15 ]. Considering the levels of CA19-9 in our cohort of 200 patients, 58 cases (29%) had CA19-9 levels below the standard cutoff value of 37 U/mL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CA19-9 is the only serological tumor biomarker approved by the FDA for pancreatic cancer, which is far from ideal. CA19-9 may give false positive results in benign pancreaticobiliary diseases, and is not expressed in about 10% of the Caucasian population [ 11 , 12 , 13 , 14 , 15 ]. Considering the levels of CA19-9 in our cohort of 200 patients, 58 cases (29%) had CA19-9 levels below the standard cutoff value of 37 U/mL.…”
Section: Resultsmentioning
confidence: 99%
“…CA19-9 is the only serological tumor marker approved by the FDA and used routinely for the detection and monitoring of PDAC progression; it has 79–81% sensitivity and 82–90% specificity for the diagnosis of PDAC [ 11 , 12 , 13 ]. However, CA19-9 also gives false positive results in benign pancreaticobiliary diseases [ 14 , 15 ]. Several studies reported a number of non-invasive diagnostic and/or prognostic markers of pancreatic cancer that have been tested alone or in combination, such as: CA125, CEA, CEACAM1, MUC1, MIC1/GDF15, REG3A/PAP1, PKM2 and AXL, as well as auto-antibodies, fecal microbiome signatures and myeloid-derived suppressor cells [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been undertaken in order to identify the best serum biomarkers for predicting the prognosis of pancreatic ductal adenocarcinoma (PDAC) patients. Previous research has shown that carbohydrate antigen 19-9 (CA19-9) is a biomarker for recurrence and survival (4). Bilirubin, on the other hand, has an effect on the level of CA19-9.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers use a variety of adjustment formulae to optimize the indicators to increase the prediction accuracy of CA19-9. The clinical stage of the patient can indicate the size of the tumor and may suggest the degree of biliary obstruction (4). In the light of this hypothesis, we expect that adjusting CA19-9 values with clinical staging and bilirubin provides a better accurate prognostic expectation than CA19-9 alone.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with PDAC in the pancreatic head may only present with complaints of jaundice at advanced tumour stages. Furthermore, as described by Boyd et al, current diagnostic strategies seem to be unable to accurately differentiate PDAC from distal cholangiocarcinoma and malignant from benign disease in the pancreatic head [ 4 ]. The only validated biomarker that is currently used in the clinic is carbohydrate antigen 19-9 (CA19-9).…”
mentioning
confidence: 99%